The "Hypertension Approaches in the Elderly: a Lifestyle study" multicenter, randomized trial (HAEL Study): rationale and methodological protocol - Daniel Umpierre; Lucas Porto Santos; Cíntia Ehlers Botton; Eurico Nestor Wilhelm; Lucas Helal; Gustavo Zaccaria Schaun; Gustavo Dias Ferreira; Angélica Trevisan De Nardi; Lucinéia Orsolin Pfeifer; Anderson Donelli da Silveira; Carisi Anne Polanczyk; Graciele Ferreira Mendes; et al. (BMC, 2019)
Abstract Background Hypertension is a clinical condition highly prevalent in the elderly, imposing great risks to cardiovascular diseases and loss of quality of life. Current guidelines emphasize the importance of nonpharmacological strategies as a first-line approach to lower blood pressure. Exercise is an efficient lifestyle tool that can benefit a myriad of health-related outcomes, including blood pressure control, in older adults. We herein report the protocol of the HAEL Study, which aims to evaluate the efficacy of a pragmatic combined exercise training compared with a health education program on ambulatory blood pressure and other health-related outcomes in older individuals. Methods Randomized, single-blinded, multicenter, two-arm, parallel, superiority trial. A total of 184 subjects (92/center), ≥60 years of age, with no recent history of cardiovascular events, will be randomized on a 1:1 ratio to 12-week interventions consisting either of a combined exercise (aerobic and strength) training, three times per week, or an active-control group receiving health education intervention, once a week. Ambulatory (primary outcome) and office blood pressures, cardiorespiratory fitness and endothelial function, together with quality of life, functional fitness and autonomic control will be measured in before and after intervention. Discussion Our conceptual hypothesis is that combined training intervention will reduce ambulatory blood pressure in comparison with health education group. Using a superiority framework, analysis plan prespecifies an intention-to-treat approach, per protocol criteria, subgroups analysis, and handling of missing data. The trial is recruiting since September 2017. Finally, this study was designed to adhere to data sharing practices. Trial registration NCT03264443. Registered on 29 August, 2017.